Ensilage and Secondary Fermentation of Maize Stalk and Their Effect on Methane Production and Microbial Community Dynamics in Anaerobic Digestion - Huan Zhang; Puxiang Yan; Ziyao Qin; Xiaoling Zhao; Xufeng Yuan; Zongjun Cui; Jingwei Wu (Fermentation)
Ensilage is an efficient storage method for preserving maize stalks for use as biogas feedstocks. However, maize stalk silages are susceptible to secondary fermentation, which degrades feedstock quality. This study explored the effects of ensilage and secondary fermentation on methane production from maize stalk and microbial community dynamics in anaerobic digestion (AD). Both ensilage and secondary fermentation decreased the specific methane yield (SMY) of maize stalks. Ensilage inhibited the acidogenesis process in AD. Secondary fermentation reduced bacterial richness and hydrolytic activity, and thus decreased the SMY of silage. After 6 months of ensilage, 97.06% organic dry matter (ODM) and 94.28% methane yield were preserved. SF greatly reduced the storage efficiency by causing 34.11% ODM loss and 52.60% methane yield loss in 40 days. Losses in ODM or methane yield during air exposure followed the Zwietering-modified Gompertz model. Metagenomic analysis showed a shift from Ruminoccoccaceae and Lachnospiraceae to Rikenellaceae in AD of maize stalk silage following secondary fermentation. Carnobacteriaceae, Moraxellaceae, Lachnospiraceae, Porphyromonadaceae, and Corynebacteriaceae were positively correlated with the content of water-soluble carbohydrates, whereas Anaerolineaceae and Ruminococcaceae were positively correlated with total organic acid content in stalks.